Adapting a codesign process with young people to prioritize outcomes for a systematic review of interventions to prevent self‐harm and suicide. (6th May 2022) - Knowles, Sarah; Sharma, Vartika; Fortune, Sarah; Wadman, Ruth; Churchill, Rachel; Hetrick, Sarah
Abstract: Background: Research and clinical outcomes that matter to people with lived experience can significantly differ from those outcomes studied by researchers. To inform a future Cochrane review of suicide and self‐harm prevention interventions, we aimed to work with young people with relevant lived experience to agree on priority outcomes. Design: Four participatory codesign workshops were completed across two sites (New Zealand, United Kingdom) with 28 young people in total. We iteratively adapted the methods over the course of the study. Results: 'Improved coping' and 'safer/more accepting environment to disclose' were the final top‐rated outcomes. 'Reduction of self‐harm' was considered a low priority as it could be misleading, stigmatizing and was considered a secondary consequence of other improvements. In contrast to typical research outcomes, young people emphasized the diversity of experience, the dynamic nature of improvement and holistic and asset‐based framing. Methodologically, dialogue using design materials (personas) to thematically explore outcomes was effective in overcoming the initial challenge of disparate quantitative ratings. Discussion: The results will directly inform the development of a Cochrane review, enabling identification of whether and how outcomes of most importance to young people are measured in trials. Rather than producing discrete measurable outcomes that could be easily added to the systematic review, the young people challenged the academic conceptualization of outcomes, with implications for future evidence synthesis and intervention research, and for future codesign. Patient or Public Contribution: Young people with lived experience were codesigners of the outcomes, and their feedback informed iterative changes to the study methods.